PENGINDERAAN JAUH UNTUK PEMANTAUAN KEKERINGAN LAHAN SAWAH - Zubaidah, Any; Dirgahayu, Dede; Pasaribu, Junita Monika (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
Information of drough condition, especially in the paddy field is much needed in order to manage food availability in a certain area. Drough monitoring in paddy field can be generated by using MODIS and TRMM data. The purpose of this paper is to show spatial information of drough prone condition in the paddy field in East Java Province especially on July – September 2011. Data used in this paper is Terra/Aqua MODIS (Moderate Resolution Imaging Spectroradiometer) and TRMM data in the same period on July – September 2011, standard extensive field and administration map of East Java Province. The method which is used in this paper is combining EVI (Enhance Vegetation Index) with LST (Land Surface Temperature) to obtain ETP (Potential Evapotranspiration) and make Meteorologist and Agronomist Drough parameter. Furthermore, processing of reflectance data was done to calculate Hydrologist Drough parameter. After that, this drough condition was classified into five class, namely non dry, mild, moderate, heavy and puso (crop failure).